Persepsi Masyarakat terhadap Pembangunan Rumah Susun di Bali - Suprijanto, Iwan (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2009)
Issue of the importance of multi-storey housing building appear as a solving on some of the urban problematic mainly in settlement issue. Some of societies considered that multi-storey housing able to solve parts of the problem. By vertically building housing, there will be reduction of farming land conversion; the ecosystem environmental will be revitalize, and affordable housing for the urban poorer communities. Nevertheless, other sides of societies are not being able to accept the multi storey housing concept because they consider it is inappropriate to the culture and social characteristic of the communities. Instead of solving the problem, this inappropriate concerned to create new problem rather than solving it. This research is explorative, perimeter on the investigation about communities perception on multi-storey housing build in Bali.